PEMBERDAYAAN UMKM DALAM MENINGKATKAN PENDAPATAN PADA MASA PANDEMI COVID-19 DI KELURAHAN KEMANISAN - Gatot Hartoko; Rika Kartika; Fatari Fatari; Muhammad Saleh; Aditya Aditya; Ajeng Monica (LPPM Universitas Bina Bangsa, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the productive economic sectors that can be a source of income for individuals. MSME activists in the 4.0 era are required to be more creative in innovating, both in terms of products and marketing through digital marketing. The existence of the COVID-19 pandemic which lasted quite a long time, had a huge impact on the MSME sector, due to limitations in conducting offline commerce. MSME activists and the surrounding community in the Kemanisan Village, Curug Sub-district were also affected by the COVID-19 pandemic, namely the decline in income levels and sluggish economic activity. Potential resources in Kemanisan Village are Chicken and Bamboo Shoots, quite high competition in sales of chicken and bamboo shoots. This community service is carried out to empower MSMEs in increasing incom.. The method of implementation is carried out by the experimental method, namely providing insight and direct experimental practice related to product innovation of processed chicken and bamboo shoots. In addition, it also uses the lecture method about digital marketing through the Shopee marketplace. Based on a series of activities that have taken place in community service activities in Kemanisan Village, several results were obtained, including the activity participants were able to produce shredded chicken products and meatballs aci bamboo shoots in packaging to operate shopee for online marketing, so that they had the opportunity to increase income